AB1050 Comparative study between ultrasonographic assessment and clinical examination in rheumatoid arthritis with optimized biological therapy and non biological treatment. (15th June 2017) - Martínez, R; Fernández, M; Rubio, E; Almagro, R Menor; Hernández, B; Povedano, J
Abstract : Background: In rheumatoid arthritis (RA), patients in low activity disease or clinical remission measured by disease activity indexs can present subclinical activity by ultrasound study. The ultrasonographic inflammation in examination of joints is an important predictive value of structural damage. Objectives: The aim of our study was to describe subclinical ultrasonographics activity in patients with RA in low disease activity or clinical remission, with optimized biological therapy and non biological treatment. Methods: Transversal and longitudinal study describing the ultrasonographic changes in gray scale and doppler in parallel with blind clinical evaluation. We included patients with RA according to ACR/EULAR classification criteria in low activity disease or remission measured by DAS28, under optimized biological therapy at least for 6 months and non biological treatment. They were sent by their usual clinician, making a random selection. They were evaluated in the same day by a rheumatologist and blind sonographer. VAS, VGP, VGM, HAQ, tender joints count, swollen joint count, CDAI, SDAI and DAS28 were evaluated. Regarding the ultrasound, were evaluated synovitis and doppler in 12 joints (wrists, second to fifth MCF and fifth bilateral MTF). The comparison between clinical examination and ultrasonography test was performed by the kappa index, with satisfactory value of >0, 6. Results: A total of 69 patients were included, 35 with optimized biological therapy and 34 non biological treatment. The median optimization time was 12 months. The baseline characteristics only offered stadistical significance in swollen joint count and average time of disease (table 1 ). The concordance study between clinical joint exploration and ultrasonographic examination showed a higher kappa index in patients with optimized biological therapy: 0, 52 in gray scale and 0, 40 in doppler. In patients without biological therapy showed an index kappa =0.17 by the gray scale test, and kappa index =0.26 by doppler. Conclusions: Our results show the existing discrepancy between the clinical examination and ultrasonographic test in patients in low disease activity/remission by DAS28, even more with the use of doppler. In the comparison of both groups we observed an increase in the difference in those who did not receive biological therapy. In patients with optimized biological teraphy, with higher swollen joint count in physical examination, kappa index was near of normality in grayscale. The detection of subclinical joint damage is often undertreated, showing ultrasound as a noninvasive technique of great help reducing joint damage. Disclosure of Interest: None declared